2019
DOI: 10.4067/s0719-81322019000200053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reduced amino acids diets added with protected protease on productive performance in 25-100 kg barrows

Abstract: The objective of this research was to evaluate the effect of adding protected protease to low-amino acids (AA) diets on the growth performance of barrows. Three decreasing levels of AA (protein levels), with or without the addition of protease were fed to 48 hybrid barrows (27.42±3.48 kg initial body weight). The experimental design was a completely randomised with a factorial arrangement of treatments. An analysis of variance was performed with GLM of SAS and the means comparison was performed with Tukey test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“… Figueroa et al (2019) assessed the effects of adding protected protease to low AA diets on the growth performance of grow-finisher pigs. Reducing SID lysine content 0.05% and 0.10% relative to the control diet and with a proportionate reduction in concentrations of the remaining AA in the diet, the authors reported no effect of protected protease addition into grow-finish diets on pig growth performance.…”
Section: Discussionmentioning
confidence: 99%
“… Figueroa et al (2019) assessed the effects of adding protected protease to low AA diets on the growth performance of grow-finisher pigs. Reducing SID lysine content 0.05% and 0.10% relative to the control diet and with a proportionate reduction in concentrations of the remaining AA in the diet, the authors reported no effect of protected protease addition into grow-finish diets on pig growth performance.…”
Section: Discussionmentioning
confidence: 99%